Representaciones sociales de la meditación budista en practicantes de Lima Metropolitana - García Ugaz, Beatriz (2019)
The purpose of this research is to know what social representations practitioners have about Buddhist meditation, with the aim of analyzing them and obtaining a deeper explanation of the phenomenon and its diffusion in Metropolitan Lima. To achieve the objectives, an exploratory study with phenomenological design was carried out, involving 13 individuals who practiced Buddhist meditation for at least 5 years and resided in Metropolitan Lima, who underwent a semi-structured interview and whose data were processed through qualitative analysis. The results of the exploration showed that, in the first place, there are mechanisms that help its formation and configuration, such as direct personal experience and channels of transmission of representations. Secondly, practitioners have represented Buddhist meditation as a habit that contributes to the development of cognitive, emotional and interpersonal skills. In the same way, they represent it as a practice that positively impacts on psychological, spiritual and corporal aspects. These representations are factors that contribute to the dissemination of Buddhist meditation, based on its interactive nature and supported by the transmission of its effects and areas of action, especially through word of mouth marketing and media on the internet and networks social.